Calorie Restriction with a High-Fat Diet Effectively Attenuated Inflammatory Response and Oxidative Stress-Related Markers in Obese Tissues of the High Diet Fed Rats - Seungae Park; Na-Young Park; Giuseppe Valacchi; Yunsook Lim (Mediators of Inflammation)
Obesity characterized by increased mass of adipose tissue leads to systemic inflammation. Calorie restriction (CR) improves parameters associated with immune response and antioxidant defense. We hypothesized that CR with a high fat diet (HFCR) regulates local and systemic inflammation and oxidative stress damage in a high fat diet induced obesity (HF group). We investigated effect of HFCR on inflammation and oxidative stress-related markers in liver and adipose tissues as well as adipokines in plasma. HFCR lowered liver triglyceride levels, total cholesterol levels, and the plasma leptin/adiponectin ratio to normal levels and improved glucose tolerance. HFCR also improved fatty liver and normalized adipocyte size and morphology. HFCR reduced lipid peroxidation and decreased the expression levels of inducible nitric oxide synthetase, cyclooxygenase-2, NF-E2-related factor, and heme oxygenase-1 in the liver. Moreover, HFCR suppressed the expression levels of C- reactive protein and manganese superoxide dismutase in the adipose tissue in the HF group. These results suggest that HFCR may have beneficial effects on inflammation and oxidative stress as well as lipid profiles in the HF diet induced obesity. Moreover, HFCR may be a good way to increase compliance in obese patients and to prevent obesity induced complications without changes in dietary pattern.